2022
DOI: 10.14479/jkoos.2022.27.4.297
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Ocular Dryness and Optical Quality when Watching Movies Using a Virtual Reality Device

Abstract: Purpose: The use of computers spread among the population, both for work and leisure purposes. This poses an increased risk factor for dry eye disease, a multifactorial disease influencing the surface of the eye. With the recent increasing usage of head-mounted displays, it is critical to determine whether or not they have the same impact on the tear film as conventional screens. Methods:The experiment was divided into three parts, where ten subjects participated. A baseline measurement was taken on the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…This could lead to subjective symptoms of dry eyes. Based on the outcome of the score (OSDI) questionnaire, it was reported that the aforementioned symptoms increased when using VR devices [12]. Prolonged use of digital screens, known as visual display terminals (VDTs), has become common, leading to increased visual complaints like eye strain and dryness.…”
Section: Introductionmentioning
confidence: 99%
“…This could lead to subjective symptoms of dry eyes. Based on the outcome of the score (OSDI) questionnaire, it was reported that the aforementioned symptoms increased when using VR devices [12]. Prolonged use of digital screens, known as visual display terminals (VDTs), has become common, leading to increased visual complaints like eye strain and dryness.…”
Section: Introductionmentioning
confidence: 99%